Factors associated with adverse pregnancy outcomes among women who delivered at intermediate hospital oshakati, Namibia - Mungoba, Teopolina Natangwe; Mitonga, Kabwebwe Honore; David, Sabina Aishe; Musekiwa, Alfred; Nakale, Tuyakula (International Journal of Medicine, 2016)
Background: Globally, the leading cause of death among females aged 15-49 years old is maternal mortality. More than 1,500 women die each day from pregnancy related causes resulting in an estimated 550,000 maternal deaths annually. We identified risk factors associated with adverse pregnancy outcomes.Methods: We conducted a descriptive, cross-sectional study, in which we administered a structured questionnaire through face to face interviews. We also applied the multivariate logistic regression model to determine factors associated with adverse pregnancy outcomes.Results: We enrolled a total of 306 pregnant women of whom 50% (n=153) were 12-19 years old and 50% (n=153) were 20-45 years old. Maternal death occurred only in the 20-45 years old mothers (6/153, 3.9%). In multivariate analysis, living in a rural area (aOR2.00, 95% CI: 1.08 to 3.69, p=0.027), shorter gestational period [32-37 weeks] (aOR4.84, 95% CI: 2.31 to 10.14, p=0.0007), haemoglobin level <10gm% (aOR3.87, 95%CI: 1.79 to 8.39, p=0.001), obesity [BMI â‰¥ 30 kg/m2] (aOR4.89, 95% CI: 1.38 to 17.37, p=0.014) and moderately high blood pressure [SBP/DBP of 150/100-159/109] (aOR15.15, 95% CI: 1.78 to 128.68, p=0.013) were significantly associated with adverse pregnancy outcomes.Conclusion: In this study, we identified living in a rural area, shorter gestational period, haemoglobin level < 10gm%, obesity, and having moderately high blood pressure to be risk factors for adverse pregnancy outcomes. All the maternal deaths were in the 20-45 years old pregnant mothers. We recommend educating women on these risk factors in order to reduce the burden of adverse pregnancy outcomes.